Non-nicotine constituents in e-cigarette aerosol extract attenuate nicotine's aversive effects in adolescent rats. (1st October 2019) - Harris, Andrew C.; Muelken, Peter; Swain, Yayi; Palumbo, Mary; Jain, Vipin; Goniewicz, Maciej L.; Stepanov, Irina; LeSage, Mark G.
Highlights: We tested aversive effects of e-cigarette (EC) aerosol extracts in adolescent rats. Nicotine alone produced significant conditioned taste aversion in adolescents. Vuse Menthol EC extract had attenuated aversive effects compared to nicotine alone. Aversive effects of Aroma E-Juice EC extract did not differ from nicotine alone. Non-nicotine constituents in certain EC extracts may attenuate nicotine aversion. Abstract: Background: Development of preclinical methodology for evaluating the abuse liability of electronic cigarettes (ECs) in adolescents is urgently needed to inform FDA regulation of these products. We previously reported reduced aversive effects of EC liquids containing nicotine and a range of non-nicotine constituents (e.g., propylene glycol, minor tobacco alkaloids) compared to nicotine alone in adult rats as measured using intracranial self-stimulation. The goal of this study was to compare the aversive effects of nicotine alone and EC aerosol extracts in adolescent rats as measured using conditioned taste aversion (CTA), which can be conducted during the brief adolescent period. Methods and Results: In Experiment 1, nicotine alone (1.0 or 1.5 mg/kg, s.c.) produced significant CTA in adolescent rats in a two-bottle procedure, thereby establishing a model to study the effects of EC extracts. At a nicotine dose of 1.0 mg/kg, CTA to Vuse Menthol EC extract, but not Aroma E-Juice EC extract, was attenuated compared to nicotine alone during repeated two-bottle CTA tests (Experiment 2a). At a nicotine dose of 0.5 mg/kg, CTA to Vuse Menthol EC extract did not differ from nicotine alone during the first two-bottle CTA test but extinguished more rapidly across repeated two-bottle tests (Experiment 2b). Conclusions: Non-nicotine constituents in Vuse Menthol EC extracts attenuated CTA in a two-bottle procedure in adolescents. This model may be useful for anticipating the abuse liability of ECs in adolescents and for modeling FDA-mandated changes in product standards for nicotine or other constituents in ECs.